The "mystery" of the train station: The importance of a forensic approach to a rare case of survival after a train-pedestrian collision. (April 2023) - Amadasi, Alberto; Franceschetti, Lorenzo; Bolsi, Giulia; Mazzarelli, Debora; Zoja, Riccardo
Abstract: In the early morning a 28-year-old man was found lying on the tracks of a railway station with head injuries and fractures of the cervical spine resulting in permanent quadriplegia. He was in a club about 1 km away until about 2 h earlier and did not have any recollection of what could have happened. Was he the victim of an assault, did he fall down or was he hit by a passing train? The solution to this "mystery" came from a forensic evaluation that included the forensic branches of pathology, chemistry, merceology and genetics as well as the scene evaluation. Through these different steps, the role of a railway collision in determining the injuries was ascertained and a possible dynamic was postulated. The presented case is an expression of the importance of the different forensic disciplines and the difficulties the forensic pathologist encounters when analysing such peculiar and rare cases. Highlights: Forensic pathology usually deals with railway fatalities. Cases of survival from a railway collision are extremely rare. Clinical forensic pathologist may rely on different forensic sciences. Adequate reconstruction of dynamics is a multidisciplinary approach.